Low- and High-Frequency Repetitive Transcranial Magnetic Stimulation Effects on Resting-State Functional Connectivity Between the Postcentral Gyrus and the Insula - Addicott, Merideth A. (Brain Connect, 2019)
The insular cortex supports the conscious awareness of physical and emotional sensations, and the ability to modulate the insula could have important clinical applications in psychiatry. Repetitive transcranial magnetic stimulation (rTMS) uses transient magnetic fields to induce electrical currents in the superficial cortex. Given its deep location in the brain, the insula may not be directly stimulated by rTMS; however, rTMS may modulate the insula via its functional connections with superficial cortical regions. Furthermore, low- versus high-frequency rTMS is thought to have opposing effects on cortical excitability, and the present study investigated these effects on brain activity and functional connectivity with the insula. Separate groups of healthy participants (n = 14 per group) received low (1 Hz)- or high (10 Hz)-frequency rTMS in five daily sessions to the right postcentral gyrus, a superficial region known to be functionally connected to the insula. Resting-state functional connectivity (RSFC) was measured pre- and post-rTMS. Both 1 and 10 Hz rTMS increased RSFC between the right postcentral gyrus and the left insula. These results suggest that low- and high-frequency rTMS has similar long-term effects on brain activity and RSFC. However, given the lack of difference, we cannot exclude the possibility that these effects are simply due to a nonspecific effect. Given this limitation, these unexpected results underscore the need for acoustic- and stimulation-matched sham control conditions in rTMS research.